2021
DOI: 10.3390/biology10121337
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein Lurap1 Is Required for Cell Cohesion during Epiboly Movement in Zebrafish

Abstract: Cell adhesion and polarized cellular behaviors play critical roles in a wide variety of morphogenetic events. In the zebrafish embryo, epiboly represents an important process of epithelial morphogenesis that involves differential cell adhesion and dynamic cell shape changes for coordinated movements of different cell populations, but the underlying mechanism remains poorly understood. The adaptor protein Lurap1 functions to link myotonic dystrophy kinase-related Rac/Cdc42-binding kinase with MYO18A for actomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Li et al. have also implicated LURAP1 and MYO18A in mediating cell adhesion during epiboly movement during vertebrate embryogenesis, a fascinating potential role for both proteins 65 . In this context, Newman et al.…”
Section: Functions In Cell Morphology and Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al. have also implicated LURAP1 and MYO18A in mediating cell adhesion during epiboly movement during vertebrate embryogenesis, a fascinating potential role for both proteins 65 . In this context, Newman et al.…”
Section: Functions In Cell Morphology and Migrationmentioning
confidence: 99%
“…Li et al have also implicated LURAP1 and MYO18A in mediating cell adhesion during epiboly movement during vertebrate embryogenesis, a fascinating potential role for both proteins. 65 In this context, Newman et al reported that MYO18Aα operates at three-dimensional level to convey integrin-associated cell-matrix interactions with nuclear movement through MYH9 across the cell. 23 Work by Yu and colleagues identified the interaction of MYO18Aɑ with the p21-activated kinase 2 (PAK2) via binding of the carboxy-terminal extension of MYO18Aɑ with the PAK-interacting exchange factor βPIX.…”
Section: Role In Cell Migration Via Interactions With Lurap1 and βPixmentioning
confidence: 99%
See 1 more Smart Citation